Development of an efficient Pt/SiO2 catalyst for the transfer hydrogenation from perhydro-dibenzyltoluene to acetone - Zakgeym, Dina; Engl, Timo; Mahayni, Yazan; Müller, Karsten; Wolf, Moritz; Wasserscheid, Peter (Applied Catalysis A-General, 2022)
The storage of hydrogen in liquid organic hydrogen carriers (LOHCs) represents a safe and easy to handle storage solution for energy from renewable sources. Dibenzyltoluene (H0-DBT)/perhydro-dibenzyltoluene (H18-DBT) is a promising LOHC system due to its low flammability, wide liquid range and high storage density for hydrogen. However, this LOHC system requires high temperature heat (typically > 250 °C) for hydrogen release, which lowers the efficiency of the storage cycle if no appropriate source of waste heat is available. This disadvantage can be mitigated by transfer of the hydrogen onto an acceptor molecule such as acetone at mild temperatures, forming isopropanol which can be used as fuel in direct fuel cell concepts or represents a valuable chemical product. Herein, we present the development of an active and selective platinum on silica (Pt/SiO2) catalyst for the transfer hydrogenation of acetone using perhydro-dibenzyltoluene as the sole source of hydrogen. Relevant catalyst design parameters, such as the optimal pore size, Pt loading, reduction and oxidation temperatures/times, are identified and their influence on the catalyst morphology and performance is discussed.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Acetone; Aldol formation; Dibenzyltoluene; LOHC systems; Transfer hydrogenation